Spatial proteomics defines the content of trafficking vesicles captured by golgin tethers - John J. H. Shin (Nature Portfolio, 2020)
The vesicles that transport proteins between intracellular organelles are small, short-lived, and elusive. Here, the authors show that capture of these vesicles through relocalizing tethers to mitochondria allows their contents to be characterised by organelle proteomics.